Maria ebook A novel of maria von trapp. - Moran, Michelle (2024)
NATIONAL BESTSELLER • Maria von Trapp. You know the name and the iconic songs, but do you know her real story? This dramatic novel, based on the woman glamorized in The Sound of Music, brings Maria to life as never before. “As immersive, heartbreaking, and ultimately redemptive as the musical . . . This one is not to be missed.”—Allison Pataki, author of Finding Margaret Fuller In the 1950s, Oscar Hammerstein is asked to write the lyrics to a musical based on the life of a woman named Maria von Trapp. He’s intrigued to learn that she was once a novice who hoped to live quietly as an Austrian nun before her abbey sent her away to teach a widowed baron’s sickly child. What should have been a ten-month assignment, however, unexpectedly turned into a marriage proposal. And when the family was forced to flee their home to escape the Nazis, it was Maria who instructed them on how to survive using nothing but the power of their voices. It’s an inspirational story, to be sure, and as half of the famous Rodgers & Hammerstein duo, Hammerstein knows it has big Broadway potential. Yet much of Maria’s life will have to be reinvented for the stage, and with the horrors of war still fresh in people’s minds, Hammerstein can’t let audiences see just how close the von Trapps came to losing their lives. But when Maria sees the script that is supposedly based on her life, she becomes so incensed that she sets off to confront Hammerstein in person. Told that he’s busy, she is asked to express her concerns to his secretary, Fran, instead. The pair strike up an unlikely friendship as Maria tells Fran about her life, contradicting much of what will eventually appear in The Sound of Music . A tale of love, loss, and the difficult choices that we are often forced to make, Maria is a powerful reminder that the truth is usually more complicated—and certainly more compelling—than the stories immortalized by Hollywood.